The exact gossiping problem for six messages - Paderanga, Melissa D. (2003)
The integration of the telecommunication industry and computer industry is a distinct feature of the advancements of a third-wave technology. Communication, hence, the transfer of information between a source and a receiver, has portrayed a significant role in information dissemination. Information dissemination develop into different modes as one-to-one communication such as telegraph, telephone calls, conversations, radio communications and gossiping among others; one-to-many communication such as broadcasting, SMS applications, and multimedia messaging services; and many?to-many communication through groupwares, videoconferencing, and multimedia chat forums. For example, in teleconferencing, people in different regions are allowed to attend meetings using telephone lines. Gossiping and broadcasting are two problems of information dissemination described for a group of individuals connected by a communication network through the concepts of graph. In a gossiping problem, each node (corresponding to each of the n person) has a unique piece of information that must be transmitted to all other nodes. This study presents a mathematical model, for a given number of exactly n persons, denoted by E(n,k) for each n person to know exactly k messages. This study focuses on the minimum number of calls of E(n,k) for k=6 messages and for all values of n.